(untitled) (Journal Of Educational and Psychological Researches, 2019)
Abstract The current research aims to identify the impact of triangular bridging strategy in the acquisition of sociology of fourth-stage students. To achieve the research objective, the following null hypotheses were adopted: there are no statistically significant differences at a significance level (0, 05) between the average grades of the experimental group students who studied the triangular bridging strategy in acquiring concepts of sociology and average grades of the control group. The researcher has selected the fourth-stage students from Alexandronah School for girls that s related to the Directorate General of Baghdad the sample consisted of (87) students at literary branch distributed into (44) students as the experimental group and (43) students as the control group. The researcher designed a test as a tool to measure the acquisition of concepts; which was consisted of (39) multi-choice questions. The results showed that the experimental group is statistically significant compared to the control group. Keywords: 3-2-1 strategy, concepts, Sociology.